Pengaruh Kemampuan Komunikasi Interpersonal dan Kecerdasan Sosial Terhadap Prestasi Belajar PKN Siswa SD Kelas V - suherli, nada; djuwita, puspa; juarsa, osa (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2020)
This study aims to determine the effect of interpersonal communication skills and social intelligence on the PKn learning achievement of elementary school students in class V of the Cluster IX Lubuklinggau. This type of research is quantitative research using multiple linear regression models. The population in this study were all elementary school students in Group IX of Lubuklinggau accredited A as many as 2 elementary schools with 115 students. The sample in this study were 58 students taken proportionally. Data collection techniques and instruments in this study using a questionnaire. Data analysis techniques using multiple linear regression formula and t test. The results of this study indicate that Fcount (27.495) is greater than Ftable (4.02) at a significant level ? = 0.05. This shows that interpersonal communication (X1) and social intelligence (X2) together influence the learning achievement. Thus it can be concluded that there is an influence of interpersonal communication skills and social intelligence on the learning achievement of PKn students in the fifth grade of Class V Cluster IX Lubuklinggau. This type of research is quantitative research using linear regression models.